Photodynamic Therapy of Oligoethylene Glycol‐Dendronized Reduction‐Sensitive Porphyrins. Issue 9 (12th June 2017) - Ju, Mingjie; Pang, Jundi; Xu, Ligong
Abstract : Graphene oxide (GO) and its functionalized derivatives have attracted increasing attention in medical treatment. Herein, a reduction sensitive PEI‐GO‐ SS ‐TPP was synthesized for photodynamic therapy. More than 80% porphyrin release was observed in the presence of 10 mmolL −1 DTT in one day. The confocal laser scanning microscopy confirmed that the cell uptake efficiency of PEI‐GO‐SS‐TPP was remarkably enhanced as compared to free porphyrin which was significantly dependent on incubation time. For photodynamic therapy, GSH‐OEt could effectively increase the photodynamic therapy efficiency of PEI‐GO‐ SS ‐TPP. Compared with free porphyrin, the toxicity from PEI‐GO‐ SS ‐TPP is much higher with a low IC50 (2.1 µg/mL) value. All results indicate that the PEI‐GO‐ SS ‐TPP PSs are promising for photodynamic therapy. Abstract : A reduction sensitive functionalized graphene oxide PEI‐GO‐SS‐TPP was synthesized. The carrier PEI‐GO could effectively enhance the uptake efficiency of porphyrin. Compared with free porphyrin, the toxicity from PEI‐GO‐ SS ‐TPP is much higher with a low IC50 value, indicating that the PEI‐GO‐SS‐TPP PSs are promising for photodynamic therapy.